Contribution of genomics to bacterial pathogenesis. - Field, D; Hood, D; Moxon, R (1999)
Genomics is changing the landscape of modern biology. The impact is far-reaching because it provides both the most economical means of acquiring large amounts of information and because it has forced the creation of new technologies to exploit this information. Five of the six genomes published in the year from August 1998 to August 1999 were human pathogens, all of which are highly host-adapted. Four of these are obligate intracellular pathogens and the study of these genomes is providing novel insights into the intricacies of pathogen-host interactions and co-evolution. These genomes are also significant because they mark the beginning of an important trend in the sequencing of closely related genomes, including the sequencing of more than one strain from a single pathogenic species. As comparative genomics truly comes of age, the ability to compare the genomes of pathogenic and non-pathogenic organisms will hopefully provide insight into what makes certain bacterial strains and species pathogens.